Investigates the impact of the value of machinery and buildings on the allocation of maintenance expenditure in work units under the auspices of the Ministry of Education and Culture. - Elida Murni; Nurmala Ahmar; Darmansyah (prodima@fe.uika-bogor.ac.id, 2025)
The objective of this study is to analyze the effect of machinery, equipment, and building values on the allocation of maintenance expenditures in work units within the Ministry of Education and Culture (period 2016-2019). The present study utilizes secondary data, in the form of financial reports, namely the Balance Sheets for the 2016 to 2018 Fiscal Years and the Budget Realization Reports for the 2017 to 2019 Fiscal Years, sourced from the Ministry of Finance website. The Ministry of Education and Culture comprises 96 work units within its purview. The data analysis techniques employed in this study encompass descriptive analysis, data quality testing, and hypothesis testing. The data were analyzed using SPSS (Statistical Package for the Social Sciences) and multiple regression analysis. The findings indicate that the value of machinery and building equipment exerts a significant and positive influence on the allocation of maintenance spending in work units within the Ministry of Education and Culture during the period 2016-2019.